Pengaruh Motivasi, Disiplin Kerja dan Kepuasan Kerja, terhadap Kinerja Karyawan PT. Digital XYZ - Elviana, Rina; Santoso, Nurhadi; Atikah, Aat; Yuriyatun, Fitri (Dinasti Review, 2023)
This research investigates the influence of motivation, work discipline and job satisfaction on workplace performance. Through a careful review of the literature, this study illustrates the complex relationship between intrinsic and extrinsic motivational factors, levels of work discipline, and levels of job satisfaction on individual and group performance achievement. Various psychological and management theories are utilised to understand how motivation, discipline and job satisfaction interact to shape optimal performance in the work environment. Findings from various studies show that high motivation, good levels of discipline, and adequate job satisfaction can have a positive impact on productivity, work quality, and overall performance. However, there is complexity and variation in the influence of these factors depending on the organisational and individual context. Thus, an in-depth understanding of the relationship between motivation, work discipline, job satisfaction and performance is important in developing effective management strategies to improve individual and organisational performance. Results of this article: 1) Motivation affects performance; 2) Work Discipline has an effect on Performance; and 3) Job Satisfaction has an effect on Performance.